2019
DOI: 10.1002/jcsm.12444
|View full text |Cite
|
Sign up to set email alerts
|

Gait speed as a mediator of the effect of sarcopenia on dependency in activities of daily living

Abstract: Background Sarcopenia in older adults is strongly associated with an increase in dependency in activities of daily living (ADL) and with a decline in gait speed. Interestingly, gait speed has been shown to independently predict mortality. In this context, our study aimed to explore the mediator role of gait speed on the relationship between sarcopenia and dependency in ADL. Methods A cross‐sectional study was conducted in Colombia, 19 705 older adults with a mean age of 70 years, 55.6% women, 16.1% with sarcop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
58
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(65 citation statements)
references
References 41 publications
4
58
1
2
Order By: Relevance
“…As shown in several other studies, a decrease in BMI is often indicative of a decrease in the muscle strength of the limbs (Perna et al, 2015;Rondanelli et al, 2017), and patients with sarcopenia generally have relative low BMI (Perez-Sousa et al, 2019). Therefore, a decline in BMI is an important manifestation of sarcopenia in patients undergoing surgery after fracture.…”
Section: Discussionmentioning
confidence: 78%
“…As shown in several other studies, a decrease in BMI is often indicative of a decrease in the muscle strength of the limbs (Perna et al, 2015;Rondanelli et al, 2017), and patients with sarcopenia generally have relative low BMI (Perez-Sousa et al, 2019). Therefore, a decline in BMI is an important manifestation of sarcopenia in patients undergoing surgery after fracture.…”
Section: Discussionmentioning
confidence: 78%
“…A well-known meta-analysis of 2888 older people set the minimum health threshold for gait speed at ≥ 0.8 m/s [ 21 ]. The promotion of physical exercise programs can prevent or even reverse the loss of functional capacity associated with sarcopenia if they emphasize improving the gait speed of the older population [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…As shown in several other studies, a decrease in BMI is often indicative of a decrease in the muscle strength of the limbs, 32,33 and patients with sarcopenia generally have relative low BMI. 34 Therefore, a decline in BMI is an important manifestation of sarcopenia in patients undergoing surgery after fracture. In addition, studies have also shown that very low weight is closely related to the occurrence of sarcopenia.…”
Section: Discussionmentioning
confidence: 99%